Index of Harmony Inter-Religious Communities in East Kalimantan - Muhammad Rais (Analisa: Journal of Social Science and Religion, 2012)
This policy research aims to describe about the actualization and habitualization of ideology on interreligious harmony. This ideology is constructed whether through top-down state policies or local value basis which is proactively advocated by elites of religions. This research uses a survey method to gain actual and evaluative responses from the respondents which is limited for Moslem and Christian groups in East Kalimantan. The research findings depicts that perceptions of the public related to inter-religious harmony tend to be very positive, the response rate represented the average index of 0.79. Although it could not be denied that there are other facts found in this study by interviewing people at the grass roots.  These people gave different response; their responses tend to be negative which may lead to a conflict of identity between local people and migrants.